EVALUATION OF PSYCHOLOGICAL DISTRESS IN CANCER PATIENTS - Anupozu, Rashmi (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The main objective of the present study is to determine the depression and anxiety using standardized rating scales in cancer patients. Methods: This prospective observational study was performed in 120 cancer patients at a local government cancer hospital. Subjects were interviewed and data were collected using standard Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) questionnaires. The obtained data were analyzed using SPSS software version 26. Results: Out of 120 patients, 75.8% were male and 24.2% were female. The maximum number of subjects (n=66, 55%) were within the age group of 41–60 years and from the urban region (54.2%). Analyzing the depression status from the PHQ-9 questionnaire, severe depression was seen high among females (31%) when compared to males (19.8%). From the scores obtained by the GAD-7 questionnaire, it was found that males with normal anxiety (26.4%) and severe anxiety (11%) were more when compared to females. On performing regression, females were 0.572 times at a higher risk of developing depression and 2.005 times likely to have GAD when compared to males. Conclusion: The present study suggests that majority of subjects with psychiatric disorders are in the age group of 41–60 years and are from the urban region. Early screening of the cancer patients for depression and GAD using validated questionnaires such as PHQ-9 and GAD-7 and providing appropriate counseling or therapy on a timely basis helps them to manage their adverse symptoms and boosts the mental health of the subjects.